Comments on “Visual Anthropology in Latin America” - León, Christian (2012)
This article comments on the dossier of the Iconos 43 edition, which focuses on “Visual Anthropology in Latin America”. The article reviews the essays and contributions made by each one of the authors; at the same time, it raises a number of questions regarding the nature, work conditions, and lines of research existent within Latin American visual anthropology. Finally, it invites the reader to reflect on the discipline’s social role when placed in a peripheral and particular context such as Latin America.